Effectiveness of Augmented Reality in Enhancing Critical Thinking in Physics Learning: A Meta-Analysis - Martin Albertus Silitonga; Emilinannur Emilinannur (Universitas Negeri Padang in collaboration with Association of Mathematics and Natural Sciences Institution for Education of Teaching Staff Indonesia (AMLI), 2026)
This study addresses the challenge of students’ difficulty in understanding abstract concepts in physics, which often leads to low critical thinking skills. Augmented Reality (AR) has emerged as a promising technology that can provide interactive and contextual visualization to support learning. This study aims to examine the effectiveness of AR in enhancing students’ critical thinking skills in physics learning. A meta-analysis approach was employed by analyzing 24 relevant studies that met the inclusion criteria. Data were analyzed by calculating effect size using Microsoft Excel and JASP, and the results were visualized using a forest plot. In addition, moderator analyses were conducted based on education level and learning materials. The findings reveal that AR has a high level of effectiveness, with an overall effect size of 0.765. This indicates that AR significantly improves students’ critical thinking skills in physics learning. Therefore, AR can be considered an effective and innovative learning medium to support physics education.